Production of Vitamin D3-Fortified Plant-Based Meat Analogs Through High-Moisture Extrusion - Lorena S. Pinho; Ramon P. Brexó; Tatielly de J. Costa; Marcelo Thomazini; Osvaldo H. Campanella; Carmen S. Favaro-Trindade (Foods)
Incorporating vitamin D3 (cholecalciferol) into food is hampered by its high instability and low water solubility. Due to porous structure that favors absorption and carrying of micronutrients, brewer’s spent yeast (BSY) is an economically and technically attractive alternative to overcome the shortcomings of vitamin D3 incorporation. Using heat and shear-sensitive ingredients and additives in formulations remains challenging due to the high-temperature and shear conditions during industrial processes, such as extrusion. This study aimed to produce an extruded plant-based meat product enriched with cholecalciferol. Vitamin D3, free and impregnated in BSY (BSY-VitD3), was blended with pea protein and subjected to cooking extrusion. Product features were analyzed for color, texture, moisture, water activity, absorption capacity, and vitamin retention. Adding BSY-VitD3 reduced all texture profile parameters and altered colors. Furthermore, free VitD3 enhanced extruded water and oil absorption capacity. After extrusion, vitamin retention percentages in the products were 45.4 and 91.6%, for free and BSY-VitD3, respectively. After 1-month storage of the extruded products, vitamin retention was 38.9 and 85.1% for free and BSY-VitD3 samples, respectively. Blending vitamin D3 with BSY is a simple, fast, and effective process to facilitate incorporation of the vitamin in the formulation and protect it during cooking extrusion.